Kolażowa tożsamość medialna - Błaszczak, Monika (Przestrzenie Teorii, 2008)
Mirrors and screens have affected the specific of knowing, especially of dramatical characters' selfknowing. The personages are trying to walk through selfknowing, they are searching their identity asking themselves where is their "ego". They want to see their real image in the mirror reflections. The process of growing the identity up which has taken place in the confrontation with the mirror reflection that calls Lacan's interpretation, who tells about Mirror Phase as an indispensable stage of "me" moulding. But the anagnorisis can't take place anymore. The character in mirror screened space faces the problem of creating his own "ego" not only from the fragment of the reality given to him directly in the dialogue and relations with other characters but also in the face of his mirror's reflection and copies in video projections. Besides selfknowing - inspiration, the problem of selfreflection in its works also appears. The memory is also the sort of mirror where the written pictures sometimes blur. In the contexts of contemporary "screened" dramas, the identity of character reaches the stage which we can call multicomplications. The character is shown as a dynamic dramatical space - the battle between the subject sphere and the object sphere. Breakdown and the lack of cohesion become the leading rule of character's creating, where in the end looks like collage. New dramatical identity has arisen - the collage media identity.